(untitled) (Daffodil International University Journal of Science and Technology, 2011)
This article investigates the effects of radiation and heat generation on magnetohydrodynamic( MHD) natural convection flow of an incompressible viscous electrically conducting fluid along a vertically placed flat plate in presence of viscous dissipation and heat conduction. Appropriate transformations were employed to transform governing equations of this flow into dimensionless form and then solved using the implicit finite difference method with Keller box scheme. The resulting numerical solutions of transformed governing equations are presented graphically in terms of velocity profile, temperature distribution, skin friction coefficient and surface temperature and the effects of magnetic parameter (M), radiation parameter (R), Prandtl number (Pr) and heat generation parameter (Q) and viscous dissipation parameter (N) on the flow have been studied with the help of graphs. Keywords: Radiation; Heat Generation Parameter; Viscous Dissipation Parameter; MHD; Finite Difference Method; Vertical Flat Plate. DOI: http://dx.doi.org/10.3329/diujst.v6i1.9330 DIUJST 2011; 6(1): 20-29